Baobabs at the edge: 90-year dynamics of climate variability, growth, resilience, and evolutionary legacy effects - Mayne, Diana H.; Karimi, Nisa; Cruywagen, Elsie M.; Cole, Patrick; Goodall, Victoria (Frontiers in Forests and Global Change, 2022)
ABSTRACT Climate variability and resilience remain gaps in tree research, challenged by the interacting factors in climate change, long-term resilience and the influence of evolutionary legacy effects. In a multidisciplinary approach using 90-year (1930-2020) climate-growth data, we investigated the dynamics of climate variability on growth and resilience of the tropical African baobab (Adansonia digitata) at the range edge in climate-variable, southeast Africa. The main driver of climate variability, ENSO (El Niño-Southern Oscillation), triggered 83% of droughts exacerbated by positive Indian Ocean Dipole (pIOD) events. Growth over 90 years was positively correlated with maximum temperature and increased after the 1976-1977 Global Warming Shift. The influence of warming was compromised by climate variability and extreme events. Although growth is a measure of adaptive capacity, accelerated growth over the past 20 years contrasted with dehydration, canopy dieback and a novel Didymella pathogen. Resilience was contingent on high genetic diversity (polyploidy and heterozygosity) and Neotropical legacy effects of stem water storage, longevity trade-offs of low growth and recruitment, and also reproduction at SNR. Evolution of resprouting in disturbed, fire-prone ecosystems and bark regeneration increased recovery from disturbance. As resource opportunists, baobabs adopted a fast-slow survival strategy. Rainfall and warming enhanced growth while low and variable rainfall favoured a conservative, low growth-higher survival strategy. Low rainfall, climate extremes and topography increased mortality risk. Mortality was higher at lower elevations on site and regionally. Low growth may conserve the baobab in climate warming but the southern hemisphere tropics is one of two identified global hotspots with amplified hot years. The heightened disturbance predicted from increased climate variability, hot droughts and landfalling tropical cyclones magnifies mortality risk for "Africa's favourite tree".